Comparison of breastfeeding self-efficacy between exclusive and non-exclusive breastfeeding in postpartum women - Parvaneh Sarparastrazmju (Preventive Care in Nursing and Midwifery Journal)
Background: Breastfeeding self-efficacy is an important factor in initiating and continuing breastfeeding. Objectives: The present study aimed to compare breastfeeding self-efficacy between exclusive and non-exclusive breastfeeding in postpartum women. Methods: This descriptive comparative study was conducted on 228 women hospitalized in the Social Security Hospital of Zahedan who had given birth 24 hours earlier. Sampling was performed using a convenience method from March to June 2024. Data were collected using a demographic-midwifery questionnaire and the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF). Data analysis was carried out using SPSS version 22 software, employing the Mann-Whitney U and Chi-square tests. Results: The mean (SD) age of the women was 28.14 (6.7) years. Most participants were housewives (92.54%) and had a diploma or lower level of education (80.26%). The mean (SD) score of breastfeeding self-efficacy was higher in women with exclusive feeding than in those with non-exclusive feeding [49.11 (11) vs 36.9 (11.7)]. There was a statistically significant difference between the exclusive and non-exclusive feeding groups regarding breastfeeding self-efficacy (p=0.000), type of delivery (p=0.034), infant’s gender (p=0.000), and the number of breastfeeding per day (p=0.036). Conclusion: Women who gave birth while exclusively breastfeeding had higher breastfeeding self-efficacy than those who breastfed non-exclusively. To enhance breastfeeding self-efficacy, it is recommended to develop appropriate strategies for initiating and continuing breastfeeding.